Determination of the roughness after polishing using fractional design in the responce surface methodology - Kovač, Pavel; Stankov, Jelena (Journal of Production Engineering, 1984)
In this article special steel for medical equipment 4590 was considered, using response surface methodology. This procedure is applied to determine the surface roughness after turning and polishing operations.